Optimalisasi E-Government pada Kawasan Free Trade Zone di Kota Batam - Wilda Mukhalladun Waruwu; Lubna Salsabila; Aqil Teguh Fathani (Penerbit Goodwood, 2023)
Purpose: The focus of this research is on the application of big data and the free trade zone in Batam. Big data is the use of technology in terms of storing big data, providing information, and providing services from a business or company profile. Batam is a free trade area and free port (free trade zone) that requires data management and data presentation with the aim of increasing its attractiveness for foreign investors. Research methodology: The research method used is a qualitative research method. Methods of data collection using review literature, natural journals, and online print media. Results: The results of the research show that Batam as a free trade zone area has begun to use big data as one of the supports for the realization of the Batam FTZ area.